THE IMPACT OF TRADE WAR BETWEEN THE UNITED STATES AND CHINA ON THE DECLINE OF PAPER EXPORTS TO INDONESIAN GOVERNMENT POLICY 2018-2020 - Damar Mili; Umi O. Retnaningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The trade war between the United States and China leads to Indonesian export to both countries. Indonesia is trading partner with the two countries that suffer from conflicts. This situation demands Indonesia to take actions to avoid the impact of the trade war. The declining of Indonesian export of paper raw materials to China result in finding new market. This study describe how the Indonesian government’s effort to deal with this issue.The perspective used in this research is the perspective of Neo-Liberalism, as well the analysis of the nation state level. This study used theory of hyper competitive which is able to explain the strategy of the Indonesian government to face difficult global situations and create policies to overcome problems due to the trade war between the United States and China. The analysis will use document from Indonesian Trade Promotion Centre (ITPC) Dubai, official application of the Ministry of Industry of the Republic of Indonesia, Ministry of Trade, Ministry of Communication and information, and statistical data from UN Comtrade.This research shows Indonesian government policy dealing the impact of the trade war between United States and China on the decline Indonesia’s paper export to China is try to approach to the United Arab Emirates market share by signing a momerandum of understanding (MoU) between the Ministry of Industry of the Republic of Indonesia and the Ministry of Energy and Industry of the United Arab Emirates. Keywords   : United States, China, Trade War, Indonesian Policy, Export, United Arab Emirates, Paper.